Sport Development Index (Sdi) In Wonogiri District - Kustiawan, Andri Arif; Alexander, Bimo; Hadiono, Hadiono; Putro, Ahmad Agung Yuwono; Suhartoyo, Topo (Universitas Hamzanwadi, 2022)
Purpose of this Researchto: (1) identify the level of participation of the people of Wonogiri Regency in exercising in 2022; (2) identify the level of physical fitness of the Wonogiri Regency community in 2022; (3) identify the level of sports development in Wonogiri Regency in terms of the participation index and the community physical fitness index in 2022. The research is a quantitative research with survey research methods and a descriptive evaluation approach. The research sample is the people of Wonogiri Regency who live in Wonogiri District, Ngadirojo District, and Paranggupito District and are divided into age and gender groups, with a total of 108 people. The sampling technique used followed the guidelines for the method of determining the Sport Development Index sample. Techniques for collecting data were questionnaires (questionnaires) and test techniques. Validity of the instrument.iukuriyesngiused isistandar who haveisetiin the Sport Development Index (SDI). Results research is as follows. (1) Community participation index is 0.477. The Wonogiri Regency Community Participation Index shows that the level of community participation in sports is included in the low category, (2) The Wonogiri Regency Community's physical fitness index is 0.440. The physical fitness index of the Wonogiri Regency community shows that the community's fitness is included in the low category, (3) The level of sports development in Wonogiri Regency in terms of participation and physical fitness of the community is included in the low category with an index of 0.468. In conclusion, the Participation Index, Physical Fitness and Sports Development of the Wonogiri Regency community are in the low category.